An econometric analysis of sport tourism in Thailand - Abdul Samad, Abdul Rahim (Center for Promoting Ideas, 2013)
South East Asia Games (SEA) is a sports game participated by 11-countries around South East Asia. The participating countries include Malaysia, Singapore, Indonesia, Thailand, Laos, Vietnam, Brunei, Myanmar, Philippines, and Cambodia. In year 2007, Thailand hosted the 24th SEA Games at Nakhon Ratchasima. It is an honor for Thailand being the host of the competition as this gave Thailand an opportunity to promote their country’s uniqueness and attractions. This paper highlights the empirical evidence of tourist arrival in Thailand which relates to the SEA games event. The economic factors, short-run and long-run effects of its determinants were examined using Autoregressive Distributed Lag (ADRL) approach. The results suggest that there are no determinants that have significant impact on tourist arrival in the long run, except for the dummy variable which represent SEA games. The dummy variable is significant at the level of 1-percent. Similarly, in the short run, the obtained results revealed that the dummy variable is a significant determinant of tourist arrival in Thailand. These results indicate that, the determinant of tourist arrival particularly based on the SEA games does exist. Whereas, the economic factors such as national income by participating countries of the SEA games and exchange rate are not important factors influencing tourist arrival in Thailand. Hence, by hosting major sport events such as SEA games will positively boost the tourism industry for the host country.